The impact of Digitalized Communication on the effectiveness of Local Administrative Authorities – Findings from Central European Countries in the COVID-19 Crisis - Bernhard Hirsch; Fabienne-Sophie Schäfer; Aleksander Aristovnik; Polonca Kovač; Dejan Ravšelj (Journal of Business Economics, 2022)
This paper analyses the impact of the use of digital communication tools in administrative procedures on the effectiveness of local administrative authorities during the COVID-19 pandemic. It considers COVID-19-driven changes in the legal competence of the institutional unit and administrative authorities' orientation to good governance as mediators of this relationship. By applying partial least squares structural equation modelling (PLS-SEM) to survey data (N0.167em=0.167em610) from five central European countries, we show that the accelerated use of digitalized communication tools driven by the COVID-19 situation has a positive effect on the effectiveness of local administrative authorities. Our data also indicate that the new laws, instructions and good governance driven by the COVID-19 situation – based on mostly convergent administrative traditions and European trends – partially mediate the relationship between the use of digital communication tools and administrative effectiveness. These findings do not significantly differ between participating countries and bureaucratic traditions. Consequently, the COVID-19 crisis proved to be a joint facilitator of responsive public governance that remained compliant with the rule of law, regardless of whether the national administrative systems were traditionally more legalistically or managerially oriented.
Keywords: H12; K10; 650; Local administrative authorities; COVID-19; Digitalization; Good governance; Comparative analysis; Central european countries